Increasing the role of the neighborhood in the development of small business and private entrepreneurship - Yuldasheva Dildora Kamilzhan (Zien Journals, 2022)
This article talks about increasing the role of neighborhoods in the development of small and private entrepreneurship and the opportunities created for young people engaged in entrepreneurial activities in neighborhoods.
Keywords: neighborhood; neighborhoodentrepreneurial activity; reforms; innovation